2018
DOI: 10.1016/j.foodqual.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization but not sensitization from commercial chemesthetic beverages

Abstract: Sensations such as spiciness or stinging are particularly challenging to assess in sensory evaluation tests, as sensitization (increase in intensity with repeated tasting) and desensitization (decrease in intensity with repeated tasting) phenomena can confound intensity ratings. However, much of the published work on these phenomena are with model solutions or complex meals rather than commercial beverages. Thus, we tested whether we could observe sensitization or desensitization using canned spicy ginger beer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…Also, there were no significant differences in the burning sensation based on gender or consumption frequency of carbonated beverages ( P > 0.05). The absence of desensitisation disagrees with the results of Running (2018), as it was identified that desensitisation did occur from ginger beer consumption. This result may have also occurred because different commercial varieties of ginger beer were included in the different studies.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Also, there were no significant differences in the burning sensation based on gender or consumption frequency of carbonated beverages ( P > 0.05). The absence of desensitisation disagrees with the results of Running (2018), as it was identified that desensitisation did occur from ginger beer consumption. This result may have also occurred because different commercial varieties of ginger beer were included in the different studies.…”
Section: Resultscontrasting
confidence: 79%
“…Their study led to us asking about consumption frequency and evaluating how it can affect participants' responses to ginger beer. This study by Running (2018) Evaluated the Sensitization and Desensitization Effects of Carbonated Water and Ginger Beer. It was very important to our study as we adapted their experimental design.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Beverage type effects were due to plain carbonated water being rated as fizzier than flavored carbonated waters ( p = .00064), which again should be interpreted cautiously as the plain carbonated water was always tasted first. While this effect is plausible, the higher rating for the plain water could have been amplified by desensitization effects on the later beverages (Running, 2018). Both this pattern of higher ratings for the plain carbonated water as well as the potential trend for a difference between age groups could be explained by looking at the contrast effects, which indicate that mainly the older adults were rating the plain carbonated water higher ( p = .011, vs. p = .17 for younger adults).…”
Section: Resultsmentioning
confidence: 99%
“…Our data should be considered cautiously, as the plain carbonated water was always presented first. This was intentional so that any first sample bias or desensitization effects (Running, 2018; Vickers, 1988) would influence this plain sample more than the flavored samples. However, while the order of tasting may have suppressed the sweetness and augmented the fizziness of the plain carbonated water, the prior literature on how aromas influence sensations lead us to suspect these effects would be maintained if the samples were randomized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation